(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2017)
The present study was carried out at the Pedro Franco Dávila Scientific Station, in Jauneche, Los Ríos Province, coastal Ecuador. The main goal was to estimate the diversity of large and medium size mammals in the reserve, as well as to identify priorities for their conservation. The methodologies used to estimate richness were direct observation, track traps, collection and identification of bone remains; curves of species accumulation and range abundance. The following 8 species of mammals were identified: Cebus albifrons aequatorialis categorized as Critical Endangered (CR), Alouatta palliata as Endangered (EN), Tamandua mexicana as Vulnerable (VU), Leopardus pardalis and Cuniculus paca as Near Threatment (NT), and Procyon cancrivorus as Data Deficient (DD). The species accumulation curve indicates that in spite of the intensity of samples, there is still mammal fauna to be recorded, that would suggest a defaunation process as a consequence of habitat fragmentation, and human-carnivore conflict. It is advisable to improve connectivity, phototrapping, as well as communication and environmental education activities in the community.